PENENTUAN WAKTU BAKU DENGAN METODE STOPWATCH TIME STUDY PROSES PRODUKSI MANIFOLD (UD. JAYA MOTOR PASURUAN) - Achmad Chumaedi; Abdul Wahid (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2020)
The increasing growth in the industrialized world today, companies are expected to compete and compete healthily is good in terms of quality, price, and service information to customers against the length of time a product is made. UD. Jaya is a Motor home industry engaged in the two-wheeled automotive spare parts, one innovation UD. Jaya Motor which are many devotees are manifold, the product is used for a special channel on go to drain the air from the carburetor into the engine. Problems occurred was delivery delays to the consumer due to the length of time the production is not yet in the know clearly, where the calculations only using estimates against defects. After doing the calculation the Stopwatch Time Study was obtained by that standard time process of making Manifold is 2460 seconds /41 minutes per product.